2018
DOI: 10.1038/s41388-017-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

The BET bromodomain inhibitor CPI203 overcomes resistance to ABT-199 (venetoclax) by downregulation of BFL-1/A1 in in vitro and in vivo models of MYC+/BCL2+ double hit lymphoma

Abstract: High-grade B-cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements, mostly known as double-hit lymphoma (DHL), is a rare entity characterized by morphologic and molecular features between Burkitt lymphoma and the clinically manageable diffuse large B-cell lymphoma (DLBCL). DHL patients usually undergo a rapidly progressing clinical course associated with resistance to standard chemo-immunotherapy. As a consequence, the prognosis of this entity is particularly poor with a median overall survival inferior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…Such models can be used to study processes that cannot be studied in cell lines. In this context, acquired resistance models have been established based on cell line-and patient-derived xenografts, organoids, and transgenic tumour models [115][116][117][118][119][120][121][122][123][124][125] . However, cell lines enable the establishment of a substantially larger number of models within a given timeframe and at a given cost, which is critical for studying the drug-induced heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Such models can be used to study processes that cannot be studied in cell lines. In this context, acquired resistance models have been established based on cell line-and patient-derived xenografts, organoids, and transgenic tumour models [115][116][117][118][119][120][121][122][123][124][125] . However, cell lines enable the establishment of a substantially larger number of models within a given timeframe and at a given cost, which is critical for studying the drug-induced heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Other BET inhibitors have been shown to upregulate BIM in AML cells and melanoma [ 51 , 66 ]. BIM has been suggested to play a key role in the mechanism of synergy between BET inhibition and BCL2 inhibition in primary double-hit lymphoma cells, and SCLC [ 71 , 72 ]. BIM binds BCL2, altering the balance between pro-apoptotic and anti-apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment of DHL patients is based on immunochemotherapy and intensive treatment strategies, but it does not produce a sustained remission in the majority of the cases [ 3 ]. While short-time exposure to venetoclax can trigger significant antitumoral effect in DHL cultures [ 4 ], we recently reported that prolonged exposure to the compound was associated with a decreased response of DHL cell lines at all the doses used [ 5 ]. This phenomenon was not seen in cell lines of B-cell germinal center (GCB)-diffuse large B cell lymphoma (DLBCL) origin with no concurrent MYC and BCL-2, suggesting differential compensatory mechanisms between the two NHL subtypes.…”
mentioning
confidence: 99%